Ultrasonographic follow-up of the multistep protocol for prostate cancer induction in Wistar rats - Faustino-Rocha, Ana I. (2020)
Aim: This work intended to improve the knowledge of the rat model of prostate cancer (PCa) by ultrasonographic monitoring. Materials and Methods: Male Wistar rats were divided into control (n=8) and PCa (n=14) groups. PCa development was induced in the PCa group through the sequential administration of the anti-androgenic drug flutamide, testosterone propionate and the carcinogenic N-methyl-N-nitrosourea. The prostate was evaluated by ultrasonography at five timepoints along 49 weeks of the experimental protocol. Ventral prostate lobes were observed in all ultrasonographic examinations. Results: The ventral prostate area of the control group increased gradually between the first and the last ultrasonographic examination. The ventral prostate area of PCa groups decreased due to flutamide administration and increased after androgen and carcinogen administration. The area of the dorsal prostate lobe increased between the fourth and the fifth ultrasonographic examination. In the last ultrasonographic examination, hypoechoic and anechoic lesions were observed in the PCa group. Conclusion: To our knowledge, this is the first study presenting a follow-up of rat prostatic dimensions by ultrasonography. Ultrasonography is a feasible approach for prostate cancer monitoring in experimental models.